Pengaruh Komite Audit, Kualitas Audit, Kepemilikan Institusional, Risiko Perusahaan dan Return On Assets Terhadap Tax Avoidance - Damayanti, Fitri; Susanto, Tridahus (Esensi: Jurnal Bisnis dan Manajemen, 2015)
This research aims to analyze and get empirical evidence about the effect of audit committee, audit quality, ownership institutional, corporate risk and return on assets on the tax avoidance. Sample of this research were property and real estate industries which are listed in Indonesian Stock Exchanges during 2010-2013 period. The number of property and real estate industries that were became in this study were 22 companies with 4 years observation that acquired by purposive sampling method. Hypothesis in this research were tested by multiple regression model.The result of this research showed that corporate risk and return on assets influence the tax avoidance. In the other hand, the audit quality, audit committee and ownership institutional didn’t influence the tax avoidance.DOI: 10.15408/ess.v5i2.2341